Does globalization cause a higher concentration of international trade and investment flows? - Patrick Low; Marcelo Olarreaga; Javier Suarez (World Trade Organization (WTO), 1998)
It has sometimes been argued that globalization benefits only a small number of countries, and that this leads to greater marginalization of excluded countries. This paper argues that globalization is not necessarily biased towards greater concentration in international trade and investment flows. Marginalization is more likely to be explained by domestic policies in relatively closed countries. The paper shows that among relatively open economies, the concentration of international trade and investment flows has declined over the last two decades, whereas the opposite is true among relatively closed economies. Thus, marginalization is not intrinsic to globalization.
Keywords: F11; F13; F21; 330; Globalization; international trade and investment flows concentration